Deep Crustal Seismic Reflection Profiling - Kennett, B.L.N (ANU Press, 2016)
Deep Crustal Seismic Reflection Profiling: Australia 1978-2015 presents the full suite of reflection profiles penetrating the whole crust carried in Australia by Geoscience Australia and various partners. The set of reflection data comprises over 16,000 km of coverage across the whole continent, and provides an insight into the variations in crustal architecture in the varied geological domains. Each reflection profile is presented at approximately true scale with up to 220 km of profile per page and overlap between pages. Each reflection section is accompanied by a geological strip map showing the configuration of the line superimposed on 1:1M geology. The compilation includes a suite of large-scale reflection transects groups of 1,000 km or more that link across major geological provinces, and an extensive bibliography of reports and relevant publications.